Geographic Information System of Farmer Group and Area in Samarinda City Web-Based - Pratirta Pratirta; Eko Junirianto; F. V. Astrolabe Sian Prasetya (Journal of Geomatics Engineering, Technology, and Science, 2023)
Presenting geographic data information by using a GIS (Geographical Information System), GIS is an organized series of hardware, software, geographic data, and personnel designed to efficiently obtain, store, update, manipulate, analyze, and display all forms of geographically referenced information. The difficulty of finding the location of the Farmers Group the Department of Agriculture of the City of Samarinda, it is very important to know the location, especially when the service will hold agricultural counseling for faster delivery of information, therefore an appropriate use of technology is needed to provide accurate information. The purpose of this study is to provide convenience to users in finding locations, finding routes to locations, and other information about farmer groups and their lands in the city of Samarinda. Based on the case studies in this study, it can be concluded that the author will build a web-based geographic information system for mapping farmer groups and their lands in the city of Samarinda.